The legacy of Hans W. Frei - Hunsinger, George (T&T Clark, 2022)
"This volume comprehensively demonstrates Hans W. Frei's unique contribution to theology and biblical hermeneutics. Divided into five parts, this volume first outlines the key biographical details, including a little-known interview from 1980 (here excerpted), and Frei's Jewish background while growing up in Nazi Germany. The four parts offer insights into both the centrality of biblical narrative and its fateful eclipse by modernity, as well as Frei's presuppositions on Anselm and Barth. The eminent scholars who contribute to this volume examine Frei's analytical rigor, his plea for a "high Christology" in the service of the church; and his shifting interpretations over the years of scripture's "literal sense". They ponder over Frei's relationship to his other contemporary notables such as Paul Ricoeur, Eberhard Jüngel, George A. Lindbeck and Carl F. H. Henry, along with an alternative Roman Catholic reading of the history of biblical hermeneutics over against the one he advocates"--